2010
DOI: 10.1002/adfm.200902388
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Acoustically Active Lipospheres for Magnetically Targeted Nucleic Acid Delivery

Abstract: With the aim of obtaining a carrier for combined magnetic‐field‐ and ultrasound‐targeted nucleic acid delivery, acoustically active lipospheres are prepared that comprise magnetic nanoparticles and plasmid DNA or synthetic siRNA. The lipospheres, with average diameters of 5 μm and smaller, are obtained upon shaking a mixture of soybean oil, a cationic lipid, magnetic nanoparticles, a nucleic acid, and aqueous buffer in a perfluoropropane atmosphere in a sealed vial. These lipospheres create contrast in ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 44 publications
(64 reference statements)
0
64
0
Order By: Relevance
“…Apart from lipoplexes and polyplexes, colloids, such as nanoparticles [9,10], lipospheres [11,12], and polymeric capsules [13,14] are currently being discussed as non-viral carriers for the delivery of genetic material. Polymeric capsules can be synthesized under mild conditions by a multilayer assembly of oppositely charged polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from lipoplexes and polyplexes, colloids, such as nanoparticles [9,10], lipospheres [11,12], and polymeric capsules [13,14] are currently being discussed as non-viral carriers for the delivery of genetic material. Polymeric capsules can be synthesized under mild conditions by a multilayer assembly of oppositely charged polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Few reports have been published regarding the synthesis of MMBs, which are stabilized by a polymeric, [13][14][15][16] lipid 17,18 or silica 19 shell, and the incorporation of magnetic and therapeutic NPs. In these published studies, the shells of MMBs are normally intact, which hinders MB oscillation at low-amplitude driving forces.…”
Section: Preparation Of Mmbsmentioning
confidence: 99%
“…Another report, published by Pradhan et al [3], demonstrated that the temperature of folate-targeted MLs al. [24], response needs to be 90% or higher. However, the response of the PpIX-loaded MLs to the magnetic field was higher than that of the nanoparticles, which exhibited approximately a 25% response to the magnetic field.…”
Section: In Vitro Pdt Resultsmentioning
confidence: 99%
“…Sedimentation stability and magnetic responses were determined by turbidity measurements in optical cuvettes using a spectrophotometer as previously described [24]. In brief, Fe3O4 nanoparticles were diluted with ultrapure Milli-Q water and placed in glass cuvettes; every 5 seconds up to 45 min, spectrophotometric measurements were collected at a wavelength of …”
Section: Turbidity Measurementmentioning
confidence: 99%